Surface Area of Patellar Facets: Inferential Statistics in the Iraqi Population. (28th February 2017) - Al-Imam, Ahmed; Al-Zamili, Zaid; Omar, Rawan
Abstract : Background . The patella is the largest sesamoid bone in the body; its three-dimensional complexity necessitates biomechanical perfection. Numerous pathologies occur at the patellofemoral unit which may end in degenerative changes. This study aims to test the presence of statistical correlation between the surface areas of patellar facets and other patellar morphometric parameters. Materials and Methods . Forty dry human patellae were studied. The morphometry of each patella was measured using a digital Vernier Caliper, electronic balance, and image analyses software known as ImageJ. The patellar facetal surface area was correlated with patellar weight, height, width, and thickness . Results . Inferential statistics proved the existence of linear correlation of total facetal surface area and patellar weight, height, width, and thickness. The correlation was strongest for surface area versus patellar weight. The lateral facetal area was found persistently larger than the medial facetal area, the p value was found to be <0.001 (one-tailed t -test) for right patellae, and another significant p value of < 0.001 (one-tailed t -test) was found for left patellae. Conclusion . These data are vital for the restoration of the normal biomechanics of the patellofemoral unit; these are to be consulted during knee surgeries and implant designs and can be of an indispensable anthropometric, interethnic, and biometric value.